Optimizing of Physics Learning through PjBL-STEM Model to Improve Critical Thinking Skills and Students Responsibility Attitudes - Khairun Nisah; Saminan; Muhammad Syukri; Elisa; Markisni (Jurnal Penelitian Pendidikan IPA, 2024)
Physics learning is a complex subject that required an extraordinary understanding. Based on the results of interviews at SMAN 4 DKI Jakarta, in Banda Aceh, critical thinking skill tests have not been carried out and student responsibility in following lessons.  This research aims to optimize physics learning through the PjBL-STEM model, in order to improve students' critical thinking skills and lack of sense responsible attitudes. The research design that used in this research was a one group Pretest and Post-Test Design, it was involving 120 students in grade XI. The data collection techniques are carried out through observation, interviews, questionnaires and tests that are prepared based on indicators of critical thinking skills. This research data was analyzed using the average test, N-gain and paired sample t-test. The instruments used critical thinking skills tests and responsibility attitude questionnaires. The research results show that the average N-gain 0,67 is categorized as currently. The results of the responsible attitude questionnaire are in the effective category with an average of 367.2, From the findings of this research it can be concluded that the PjBL-STEM model can optimize physics learning in improving critical thinking skills and attitudes of responsibility.